Залежнiсть швидкостi анодної iонiзацiї залiза вiд потенцiалу в сульфатних електролiтах - Вишневська, Ю.П.; Ткаленко, Д.А.; Бик, М.В.; Присяжний, В.Д. (Видавничий дім "Академперіодика" НАН України, 2007)
Based on the hypothesis of iron electrode reversibility, one can easily explain experimental Tafel slopes without taking into account multistage schemes which contain hypothesized intermediate iron hydroxo-species. On the other hand, the coincidence of the experimental slope with the calculated one by the proposed formula can evidence of iron electrode reversibility. The Tafel slope is reproduced both on the clear and partially passivated iron surface.